Changes in accommodation and convergence function after refractive surgery in myopic patients. Issue 1 (January 2023) - Meng, Can; Zhang, Yan; Wang, Shurong
In recent years, with the gradual maturation of myopia correction surgery, the changes in binocular visual function after surgery have attracted widespread attention. The accommodation of facility, the amplitude of accommodation, relative accommodation, and accommodation convergence/accommodation assembly are essential parameters for assessing binocular visual function. The changes in these parameters are significant for guiding patients in the design of the preoperative surgical approach and alleviating postoperative visual fatigue. This paper aims to guide the preoperative assessment, design, and postoperative visual training of refractive surgery in myopic patients from the perspective of changes in binocular visual function before and after myopia and surgery, which can improve accommodation and convergence function in patients after refractive surgery.